A running start: Endurance training, Zatopekian pain, and desistance from crime - Ugelvik, Thomas (European journal of probation, 2025)
In this exploratory article, we investigate the impact long-distance running may have on desistance from crime. Based on qualitative interviews with 12 individuals with offending histories, we show that a training plan may provide a sense of structure and predictability to life in general. Furthermore, regular training helps our participants cope with addiction and the risk of reverting to old drug habits. Running may also communicate or signal change to others, contributing to recognition and tertiary desistance. Finally, serious endurance training always involves a measure of pain, and our participants describe how they use negative experiences from their former lives as a pain management technique, helping them simultaneously become better runners and more successful desisters. We conclude that desistance from crime, identity change, and corporeal change might mutually strengthen each other.